1996
DOI: 10.1148/radiology.201.2.8888259
|View full text |Cite
|
Sign up to set email alerts
|

Normal and abnormal pulmonary ventilation: visualization at hyperpolarized He-3 MR imaging.

Abstract: To assess the feasibility of helium-3 magnetic resonance (MR) imaging with a three-dimensional fast low-angle shot (FLASH) sequence, He-3 gas (volume, 300 mL; pressure, 3 x 10(5) Pa; polarized up to 45% by means of optimal pumping) was inhaled by five healthy volunteers and five patients with pulmonary diseases. All breath-hold examinations (22-42 seconds) were completed successfully. Normal ventilation was depicted with homogeneous high signal intensity, lesions were depicted as causing defects, and obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
194
1
11

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(211 citation statements)
references
References 0 publications
4
194
1
11
Order By: Relevance
“…This may be due to the inability of the ventilation mechanism to physically transport sufficient amounts of PFC emulsions into the small bronchi. This also happens in 19 F MRI of lungs using PFC emulsions in ventilation (14), but should not occur with 129 Xe, 3 He, or other gases. Therefore, the 1 H spin density enhancing effect in these areas is not so significant as in other areas.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This may be due to the inability of the ventilation mechanism to physically transport sufficient amounts of PFC emulsions into the small bronchi. This also happens in 19 F MRI of lungs using PFC emulsions in ventilation (14), but should not occur with 129 Xe, 3 He, or other gases. Therefore, the 1 H spin density enhancing effect in these areas is not so significant as in other areas.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the ADC may be used to detect damage to the lung architecture. It has been reported that the ADC of 3 He gas in emphysematous regions of lungs increases compared to that in healthy lungs (4). The measurement of diffusion in the lungs has obvious diagnostic value.…”
Section: Diffusion-weighted Mri Of Lungsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter technique has shown a high signal-to-noise ratio (SNR), and permits the visualization of pulmonary arteries beyond the subsegmental branches. On the other hand, assessment of regional lung ventilation with hyperpolarized noble gas has emerged as an imaging technique for evaluating lung diseases, including tumors, emphysema, bronchiectasis, cystic fibrosis, and asthma (16)(17)(18)(19)(20)(21)(22)(23). A promising MR technique for visualizing the air spaces of the lung is the use of 3 He gas as a contrast agent.…”
mentioning
confidence: 99%